Experimental investigation of a water electrolysis Hall effect thruster. (April 2022) - Schwertheim, Alexander; Knoll, Aaron
Abstract: We conceptualise an electric propulsion system in which water is utilised as a propellant for a Hall effect thruster using in situ electrolysis. By supplying the generated oxygen to the thruster anode and the hydrogen to the neutralising cathode, poisoning of the cathode emitters is mitigated. Not only does such a system benefit from the low cost, high storability and in situ resource utilisation potential of water, but synergies with water electrolysis chemical propulsion systems allow for multi-mode chemical-electrical propulsion architectures. The water electrolysis Hall effect thruster (WET-HET) has been optimised to operate on oxygen as a proof of this concept. We perform direct thrust measurements on the WET-HET using a hanging pendulum thrust balance. The thruster was operated using oxygen mass flow rates ranging from 0.96 mg s −1 to 1.85 mg s −1, and discharge powers ranging from 490 W to 2880 W. The cathode used in this test was supplied with krypton rather than hydrogen, due to laboratory restrictions preventing compressed hydrogen and oxygen cylinders being used in close proximity. Two channel wall materials were investigated — alumina and boron nitride. It was found that the wall material had a significant impact on the thrust, with an increase of approximately 40% for boron nitride. Reconfiguration of the magnetic components of the WET-HET allows us to alter the thickness of the magnetised region within the thruster channel. We test the device in three different magnetic configurations, ranging from a traditionally thin magnetic region to complete magnetisation of the discharge channel. We find that increasing the thickness of the magnetic region reduces thrust, specific impulse, and thrust efficiency of the device. We assess the change in performance as we change the discharge channel depth of the thruster. The best performance was achieved with the shallowest channel of depth 35 mm. We find the that thrust, specific impulse and anode thrust efficiency increases linearly with power for all configurations with no obvious plateau. Greatest specific impulse and efficiency was found when mass flow was lowest. Although discharge voltage increases linearly with magnetic field strength, thrust, specific impulse and efficiency peaks at 480 Gauss. The greatest thrust measured was 38.63 ± 0.25 mN, with a maximum specific impulse of 4112 ± 36 s and a maximum anode thrust efficiency of 15.50 ± 0.27%. Highlights: Thrust measurements demonstrate the feasibility of an electrolyser fed Hall effect thruster. Improved performance is found when using boron nitride over alumina as the channel material of an oxygen Hall effect thruster. Increased magnetic thickness detriments thruster performance using oxygen as a propellant.